2022
DOI: 10.1002/ps.7216
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition profile of trifludimoxazin towards PPO2 target site mutations

Abstract: BACKGROUND Target site resistance to herbicides that inhibit protoporphyrinogen IX oxidase (PPO; EC 1.3.3.4) has been described mainly in broadleaf weeds based on mutations in the gene designated protoporphyrinogen oxidase 2 (PPO2) and in one monocot weed species in protoporphyrinogen oxidase 1 (PPO1). To control PPO target site resistant weeds in future it is important to design new PPO‐inhibiting herbicides that can control problematic weeds expressing mutant PPO enzymes. In this study, we assessed the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Trifludimoxazin had very good efficacy against PPO-resistant Amaranthus biotypes possessing the G210 deletion (Figure 11); 12 g ha −1 and 18 g ha −1 of trifludimoxazin resulted in 88% and 96% control of an Amaranthus ΔG210 biotype, respectively, while saflufenacil and lactofen at 50 g ha −1 and 420 g ha −1 , respectively, provided less than 50% control. These results suggest that trifludimoxazin can be used to control PPO-resistant biotypes with currently known target-site mutations (Porri et al 2023).…”
Section: Ppo Biochemistry and Protein Structure As Tools For Optimizi...mentioning
confidence: 97%
See 1 more Smart Citation
“…Trifludimoxazin had very good efficacy against PPO-resistant Amaranthus biotypes possessing the G210 deletion (Figure 11); 12 g ha −1 and 18 g ha −1 of trifludimoxazin resulted in 88% and 96% control of an Amaranthus ΔG210 biotype, respectively, while saflufenacil and lactofen at 50 g ha −1 and 420 g ha −1 , respectively, provided less than 50% control. These results suggest that trifludimoxazin can be used to control PPO-resistant biotypes with currently known target-site mutations (Porri et al 2023).…”
Section: Ppo Biochemistry and Protein Structure As Tools For Optimizi...mentioning
confidence: 97%
“…Trifludimoxazin has novel properties that contribute to a more stable binding compared with other PPO-inhibiting herbicides. One feature is complementary shape between ligand and protein, leading to many favorable van der Waals interactions (Porri et al 2023). In addition, the molecule is stabilized by pi-stacking effects of the ring systems.…”
Section: Ppo Biochemistry and Protein Structure As Tools For Optimizi...mentioning
confidence: 99%
“…While some weeds have evolved resistance to certain PPO-inhibiting chemistry, group 14 herbicides remain an important group of chemicals to manage weeds, 26-28 and many major agrochemical companies are developing new molecules with this mode of action. 29,30 The Agresense algorithm continues to identify novel chemical spaces with potentially new MoAs.…”
Section: Discovery Of Novel Structuresmentioning
confidence: 99%
“…Trifludimoxazin and epyrifenacil are all nonselective herbicides developed by BASF and Sumitomo Chemical Co., Ltd., respectively . What’s unique to other PPO inhibitory herbicides is that trifludimoxazin can control some PPO herbicide-resistant weeds, such as Amaranthus species. Studies have shown that PPO inhibitory herbicides have larger interaction volumes with PPO that similar to the substrate protoporphyrinogen IX would exhibit higher resistance levels than compounds with smaller interaction volumes . Trifludimoxazin has a novel warhead (6-thioxo-1,3,5-triazinane-2,4-dione), which is different from the other PPO inhibitors. , This unique structure may also contribute to its excellent herbicidal performance …”
Section: Introductionmentioning
confidence: 99%